Diagnostic value of hysterosalpingography in infertility. - Bustamante, Silvia (2015)
To determine the diagnostic value of hysterosalpingography (HSG) by investigating the correlation between the interpretation of the HSG and subsequent surgical findings. DESIGN: Descriptive, cross-sectional, retrospective study performed in the Human Reproduction Unit (HRU) of the Edgardo Rebagliati Martins National Hospital (HNERM) EsSalud. MATERIALS AND METHODS: 99 cases of patients presenting to the HRU was studied. For the interpretation of anomalies "oviduct" HSG in the classification described by Gomel and Taylor was employed, and for the collection of cases a form in which the results as "normal" or "abnormal" was recorded was designed. RESULTS. Of the 99 cases studied, in 20 cases the HSG was interpreted as "normal" and during surgery This result was confirmed in 16 cases (80%) in 4 cases (20%) was found false negative in 79 cases, the HSG was interpreted as "abnormal" and the surgical finding confirmed the presence of tubal pathology in 73 cases (92.4%), while in 6 cases (1.6%) uterine tubes of normal characteristics was found, ie false Positive Therefore, of the 99 cases, 89 of them (90%) the interpretation of the HSG was confirmed by subsequent surgical findings Conclusions.. Despite the advent of new technologies, the HSG is still a test of great diagnostic value. In this study no correlation between the interpretation of the findings and subsequent HSG laparoscopy and / or laparotomy was only 10%. The positive predictive value was 92% and sensitivity of the test reached a value of 95%.